TOTAL PHYSICAL RESPONSE DAN AUDIO LINGUAL METHOD DALAM BIMBINGAN BELAJAR BAHASA INGGRIS - Vika, Aina Diah; Yusup, Heri (DEVOSI, 2020)
In this era of globalization, more and more developments are taking place in this country. More and more foreign companies are established in Indonesia, so English is an important language that must be learned. The implementation of the activity is teaching English using the Total Physical Response and Audio Lingual Method at SD Islam Plus Al-Marzukiyah. Which in learning activities uses learning media such as audio and flash cards. Then given practice questions related to the material that has been taught. By using the Total Physical Response and Audio Lingual methods in learning English, SDI Plus Al-Marzukiyah students are more active and enthusiastic in learning English in class. They are also more enthusiastic about learning and prefer English lessons even though some of them are still in the process of getting used to learning English.